Selective Brain Cooling Reduces Motor Deficits Induced by Combined Traumatic Brain Injury, Hypoxemia and Hemorrhagic Shock - Leung, Lai Yee; Cardiff, Katherine; Yang, Xiaofang; Srambical Wilfred, Bernard; Gilsdorf, Janice; Shear, Deborah (Frontiers in Neurology, 2018)
Selective brain cooling (SBC) can potentially maximize the neuroprotective benefits of hypothermia for traumatic brain injury (TBI) patients without the complications of whole body cooling. We have previously developed a method that involved extraluminal cooling of common carotid arteries, and demonstrated the feasibility, safety and efficacy for treating isolated TBI in rats. The present study evaluated the neuroprotective effects of 4-h SBC in a rat model of penetrating ballistic-like brain injury (PBBI) combined with hypoxemic and hypotensive insults (polytrauma). Rats were randomly assigned into two groups: PBBI+polytrauma without SBC (PHH) and PBBI+polytrauma with SBC treatment (PHH+SBC). All animals received unilateral PBBI, followed by 30-min hypoxemia (fraction of inspired oxygen = 0.1) and then 30-min hemorrhagic hypotension (mean arterial pressure = 40 mmHg). Fluid resuscitation was given immediately following hypotension. SBC was initiated 15 min after fluid resuscitation and brain temperature was maintained at 32–33°C (core temperature at ~36.5°C) for 4 h under isoflurane anesthesia. The PHH group received the same procedures minus the cooling. At 7, 10, and 21 days post-injury, motor function was assessed using the rotarod task. Cognitive function was assessed using the Morris water maze at 13–17 days post-injury. At 21 days post-injury, blood samples were collected and the animals were transcardially perfused for subsequent histological analyses. SBC transiently augmented cardiovascular function, as indicated by the increase in mean arterial pressure and heart rate during cooling. Significant improvement in motor functions were detected in SBC-treated polytrauma animals at 7, 10, and 21 days post-injury compared to the control group (p < 0.05). However, no significant beneficial effects were detected on cognitive measures following SBC treatment in the polytrauma animals. In addition, the blood serum and plasma levels of cytokines interleukin-1 and −10 were comparable between the two groups. Histological results also did not reveal any between-group differences in subacute neurodegeneration and astrocyte/ microglial activation. In summary, 4-h SBC delivered through extraluminal cooling of the common carotid arteries effectively ameliorated motor deficits induced by PBBI and polytrauma. Improving cognitive function or mitigating subacute neurodegeneration and neuroinflammation might require a different cooling regimen such as extended cooling, a slow rewarming period and a lower temperature.